Reaction mechanism and kinetics for hydrolytic dehydrogenation of ammonia borane on a Pt/CNT catalyst. Issue 1 (15th July 2016) - Chen, Wenyao; Li, Dali; Wang, Zijun; Qian, Gang; Sui, Zhijun; Duan, Xuezhi; Zhou, Xinggui; Yeboah, Isaac; Chen, De
Abstract : A reaction mechanism is proposed for hydrolytic dehydrogenation of ammonia borane on a Pt/CNT catalyst. A combination of thermodynamic analysis and FTIR measurement reveals that B‐containing byproducts are mainly in the form of an NH4 B(OH)4 ‐B(OH)3 mixture rather than NH4 BO2 reported previously. The revised main reaction is NH 3 BH 3 + 4 H 2 O → NH 4 + + B ( OH ) 4 − + 3 H 2 ↑, involving the B–H, B–N, and O–H bond cleavages. Isotopic experiments using D2 O instead of H2 O as reactant or introducing D2 into the reaction atmosphere suggest the O–H bond cleavage being in the rate‐determining step, and an unfavorable occurrence of the chemisorbed H2 O dissociation (i.e., the direct O–H bond cleavage), respectively. Different reaction pathways with indirect O–H bond cleavages are analyzed, and then NH 3 BH 2 * + H 2 O * → NH 3 BH 2 ( OH ) * + H * is suggested as the rate‐determining step. Subsequently, a Langmuir–Hinshelwood kinetic model is developed, which fits well with the experimental data. © 2016 American Institute of Chemical Engineers AIChE J, 63: 60–65, 2017